Realitas Kompensasi Guru di Indonesia: Kebijakan dan Dampaknya di Tahun 2024 - Ida Rindaningsih; Eko Budi Supriyanto (Educational Research Indonesia, 2025)
This study aims to evaluate teacher compensation policies in Indonesia in 2024, focusing on professional allowances, average salaries, and teacher welfare improvement programs. This study uses the literature review (LR) method by analyzing 15 academic journal articles as the main source. The results of the analysis show that the one-time professional allowance policy has a positive impact on teachers' welfare. However, the implementation of this policy still faces challenges in terms of unequal distribution, especially between urban and rural areas, and limited access for non-permanent teachers.This study confirms the importance of transparency and better allowance management mechanisms to improve the effectiveness of the policy. The implications of this study highlight the need for deeper reforms in the management of professional allowances and the provision of ongoing training programs to support quality education. Further research is recommended to explore the long-term impact of this policy on teacher motivation and performance, and to assess the direct correlation between compensation and learning outcomes. As such, this study is expected to make an important contribution to education policymaking in Indonesia.